THE DEVELOPMENT AND IMPLEMENTATION OF BIOLOGY TEACHING KITS USING SELF REGULATED LEARNING (SRL) STRATEGIES - Agusta, Erie; ., Djukri (LPMPP Universitas Negeri Yogyakarta, 2015)
Abstract: This study was aimed to develop Biology teaching kits using Self Regulated Learning (SRL)-based strategy in senior high schools that have been validated and tested. The study was carried out by using the development strategy of Borg and Gall. The subjects were the tenth grade students of SMA Negeri 1 Sentolo in the academic year of 2014/2015. The data for the validation process and the implementation of the teaching kits were collected through questionnaires and observations. The data of the validator assessment were analyzed using the categorization formula and Borich formula. The data on the try-out were analyzed using the paired sample test. The findings were in the form of teaching kits product for Bryophyta materials for the tenth grade students. The teaching kits had been validated theoretically by experts and teachers, the lesson plans had been validated and simulated, and the teaching kits and research instruments had been tried out in a small scale and implemented in the field. Keywords: teaching kits, Self Regulated Learning (SRL) strategies PENGEMBANGAN DAN IMPLEMENTASI PERANGKAT PEMBELAJARAN BIOLOGI DENGAN STRATEGI SELF REGULATED LEARNING (SRL) Abstrak: Tujuan penelitian pengembangan ini adalah dihasilkannya perangkat pembelajaran biologi berbasis Self Regulated Learningdi SMA yang telah tervalidasi dan teruji. Metode penelitian menggunakan strategi pengembangan Borg dan Gall. Subjek penelitian perangkat pembelajaran adalah siswa kelas X SMAN 1 Sentolo. Teknik pengumpulan data dalam proses validasi dan implementasi perangkat pembelajaran menggunakan angket dan observasi. Data penilaian validator dianalisis dengan rumus kategorisasi, sedang persamaan validator terhadap lembar validasi menggunakan rumus Borich. Data hasil uji coba dianalisis dengan paired sample test. Hasil penelitian berupa produk perangkat pembelajaran pada materi tumbuhan lumut di kelas X SMA. Perangkat pembelajaran tersebut telah divalidasi secara teoretis yang dilakukan oleh ahli dan guru, rencana pelaksanaan pembelajaran tertentu telah diuji secara terbatas keterbacaan dan disimulasikan, perangkat pembelajaran dan instrumen penelitian telah diuji coba terbatas dan lebih luas. Kata kunci: perangkat pembelajaran, strategi self regulated learning